Internal regulations and institutional climate in two private institutions in Puente Piedra. Lima - Santiago Huaman, Rut (2023)
The research we have done is basic causal correlational experimental study factors lie in the use of rules and institutional climate of Excise Private Stone Bridge Puente Piedra.Lima. The sample consisted of 80 teachers at Stone Bridge Private II.EE distributed as follows among teachers and managers. The research design is transactional, correlational, causal. bivariate cross. For data collection two structured questionnaires were prepared as measurement and consists of two aspects: the use of rules and institutional climate itself. The instruments meet the qualities of validity and reliability. The study raises the following research hypothesis: The use of rules is significantly related to the institutional environment of private educational institutions in the Puente Piedra. Lima. We use Spearman Rho test for nonparametric data are ordinal type, the results allow us to reject the null hypothesis and accept the hypothesis investigated by applying the formula of Spearman Rho with a significance level of 95% found that the correlation coefficient Spearman Rho is 0.535 and the value is 0.000 p_ therefore establish that correlation has a moderate level, we see that there is a direct and a significance level of less than 0.05 for that reason we reject the null hypothesis and is accepted altern.